Exergoenvironmental analysis concerning the wood chips and wood pellets production chains. (December 2018) - Pereira, Matheus F.; Nicolau, Vicente P.; Bazzo, Edson
Abstract: The wood energy conversion into power and heating processes concerning the chips and pellets production chain is analyzed. An exergy analysis and a life cycle assessment are performed, considering the wood chips for electricity generation in a central power plant and wood pellets for distributed generation. The consumption of diesel oil, electricity and biomass itself were carried out along both production chains. The results showed the best way to avoid exergy destruction and environmental impacts based on carbon dioxide emissions. Considering the same energy conversion plant efficiency, the exergetic performance and the environmental impact are very close when both the technological routes are compared. However, taking into account a distributed generation and the high efficiency characteristic of micro cogeneration plants (combined heat and power), the pellets technological route presents a better exergetic and environmental performance. Also, a sensitivity analysis along the production chain stages have demonstrated that large variations of about 50% on the specific fuel consumption represents a very small influence on the overall exergetic efficiency, in order of just 1.5%. Highlights: The life cycle analysis as a tool to compare wood chips and wood pellets routes. Both the routes pellets and wood chips imply very close environmental impacts. The pellets and wood chips are both good alternatives for electricity generation. The wood pellet represents a promise alternative for distributed energy generation. The power plant efficiency strongly impacts on the destroyed exergy of both routes.